Theorizing the textual differences between authentic and fictitious reviews: Validation across positive, negative and moderate polarities - Banerjee, Snehasish (2017)
Purpose: The purpose of this paper is twofold: to build a theoretical model that identifies textual cues to distinguish between authentic and fictitious reviews, and to empirically validate the theoretical model by examining reviews of positive, negative as well as moderate polarities.